Nanoscale Phenomena Fundamentals and Applications - Hahn, Horst.; Sidorenko, Anatoli.; Tiginyanu, Ion. (NanoScience and Technology, 2009)
The main intention of the editors of the book is the demonstration of the intrinsic correlation and mutual influence of three important components of nanoscience: new phenomena nanomaterials nanodevices. This is the organizing concept of the book. To discover new phenomena it is necessary to develop novel nanotechnological processes for fabrication of nanomaterials. Nanostructures and new phenomena serve as the base for the development of novel nanoelectronic devices and systems. The articles selected for the book illustrate this interrelation.